Identity and lifelong learning : becoming through lived experience - Motulsky, Sue; Gammel, Jo Ann; Rutstein-Riley, Amy (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"Learning and identity development are lifetime processes of becoming. The construction of self, of interest to scholars and practitioners in adult development and adult learning, is an ongoing process, with the self both forming and being formed by lived experience in privileged and oppressive contexts. Intersecting identities and the power dynamics within them shape how learners define themselves and others and how they make meaning of their experiences in the world. I Am Who I Become: Constructing Identities as Lifelong Learners is an insightful and diverse collection of empirical research and narrative essays in identity development, adult development, and adult learning. The purpose of this series is to publish contributions that highlight the intimate and intricate connections between learning and identity. Our aim is to promote reflection and research at the intersection of identity and adult learning at any point across the adult lifespan and in any space where learning occurs: in school, at work, or in community. The series aims to assist our readers to understand and nurture adults who are always in the process of becoming. Adult educators, adult development scholars, counselors, psychologists, and sociologists, along with education and training professionals in formal and informal learning settings, will revel in the rich array of qualitative research designs, methods and findings as well as the autobiographic and narrative essays that transform and expand our understanding of the lived experience of people both like us and unlike us, from the U.S. and beyond. Volume Two, Identity and Lifelong Learning: Becoming through Lived Experience, focuses on identity and learning within informal settings and life experiences. The contributions showcase the many ways that identity development and learning occur within cultural domains, through developmental and identity challenges or transitions in career or role, and in a variety of places from assisted living facilities to makerspaces. These chapters highlight identity and learning across the adult lifespan from millennials and emerging adults to midlife and older adults. The authors examine cultural, relational and social identity exploration and learning in international contexts and within marginalized communities. Included in this volume are phenomenological and ethnographic qualitative studies, autoethnographies, case studies, and narratives that engage the reader about the myriad ways that adult development, learning, and identity connect and influence each other"-- Provided by publisher.
Keywords: Adult education -- Psychological aspects.; Identity (Psychology); Learning -- Social aspects.; Education -- Adult & Continuing Education.; Adult education, continuous learning.; elektronické knihy; electronic books